Non-invasive mechanical ventilation and epidural anesthesia for an emergency open cholecystectomy - Yurtlu,Bülent Serhan (2016)
Abstract Non-invasive ventilation is an accepted treatment modality in both acute exacerbations of respiratory diseases and chronic obstructive lung disease. It is commonly utilized in the intensive care units, or for postoperative respiratory support in post-anesthesia care units. This report describes intraoperative support in non-invasive ventilation to neuroaxial anesthesia for an emergency upper abdominal surgery.